Improvement of clean and healthy family living behavior through a home visit approach by community nurses - Syahrir, Syahrir; Ajeng Wijayanti, Lumastari; Tudang Rombeallo, Nofita; Datu, Natalia (Lembaga Penelitian dan Pengabdian Masyarakat,Politeknik Sandi Karsa, 2025)
Clean and Healthy Living Behavior (CHLB) is a critical indicator in improving public health status. However, many families have yet to fully implement CHLB practices in their daily lives, particularly in areas with limited education and access to health information. This community service program aimed to enhance family-level CHLB through a home visit approach conducted by community nurses. The method employed was an educational and participatory approach, where community nurses conducted regular home visits over three months. Each visit included direct health education, environmental observation, discussions with family members, and distribution of educational materials on CHLB. Topics included handwashing with soap, clean drinking water management, environmental sanitation, and prevention of infectious diseases. Based on local health data, the program targeted 30 households in a designated community. The results showed a significant improvement in both knowledge and practice of CHLB among the targeted families. Approximately 85% of the families demonstrated increased scores in the CHLB evaluation post-intervention. Positive behavioural changes were also observed, such as consistent handwashing before meals and after using the toilet, as well as better household waste management practices. These outcomes indicate that the home visit strategy by community nurses is an effective method for promoting health behavior change at the family level. This initiative is expected to serve as a replicable model for other communities, with the support of cross-sector collaboration. It emphasises the importance of family-based empowerment in health promotion and disease prevention efforts.